Outcome of fracture neck of femur treated by replacement surgery in the elderly - John, Decruz (2008)
In the new millennium we expect to see significant increase in life expectancy, hence an increase in elderly population. Osteoporotic related fractures such as femoral neck fractures are expected to be on the rise in incidence and carry significant morbidity and mortality . The incidence of hip fracture in Malaysia is 88 and 218 per 100,000 men and women respectively (NOF, 2005). The optimal surgical treatment of displaced femoral neck fractures in elderly with Osteoporosis remains controversial. Surgical options include prosthetic replacement (arthroplasty) and internal fixation. Arthroplasty options include hemiarthroplasty, bipolar arthroplasty, and total hip arthroplasty. The mortality rate ranged from 14%- 30% in the first year( Kenzora 1984). The decision of whether to internally fix or replace a displaced femoral neck fracture is based on life expectancy, the presence of chronic disease, bone quality, and level of function at the time of fracture, as well as on expected function. A retrospective study to assess the outcome of traumatic fracture neck of femur in the elderly aged above 65 years, from 1st January 2001 to 31st December 2005 treated by replacement arthroplasty ( Unipolar or Bipolar Hemiarthroplasty ), was conducted in Hospital Universiti Sains Malaysia. Outcome was scored via follow up at Orthopaedic clinic or telephone interview from the patient or primary care giver using the Harris Hip score ( Appendix 2). Prevalence of Osteoporosis in these patients was also reviewed using Singh Index (Appendix 3 ) .There were 45 cases of traumatic neck of femur fracture treated with hemiarthroplasty or Bipolar Hemiarthroplasty that met the criteria for this study All parameter was analysed using SPSS Version 12.0 .1 ( 2007). All data obtained from this study underwent descriptive analysis with regards to sociodemographic pattern. The mean age was 75.13 years (range, 65 to 89 years). There were 39 women (86.7%) and 6 men (13.3%).0ut of these 45 patients,15 (50 %) had returned to their premorbid ambulatory status. Functional Outcome , 7(15.6%) patients obtained a Harris Hip Score of excellent (90-100), 13(28.9%) obtained a score of good (80--89), and 11(24.4%) obtained a score of fair (70-79) ,3(6.7%) obtained a score of poor (60-69) and 1 (2.2%) obtained scores of failed (<60 ),6 represented (22.2%) patients who were not amenable for scoring. A total of 68.9 % of patients had a cumulative fair HHS score, which represented good functional outcome .Patients who had Bipolar replacement had better functional outcome .11 out of 16 patients returned to their premorbid status of being community ambulators and faired well in the Harris Hip Scores . Patients who were walking independently before trauma had a better outcome than those who needed aid to walk. Only half ( 50% ) of the patients who were initially community ambulators returned to their premorbid status . The degree of Osteoporosis was assessed using the Singh index . 33 patients (73.3%) had significant established osteoporosis with Grade 1 ( 2 patients ),Grade 2 ( 9 patients) grade 3 (22 patients) respectively. Within 1 month of surgery, 2 (4.4 %) patients had died and subsequently 7 (15.6%) had died after 1 year post operatively The functional outcome of Hemiarthroplasty was 68.9% of patients obtaining good results which is acceptable and among these cases patients who underwent Bipolar Hemiarthroplasty showed better outcome with 68.75% having excellent to good outcome as compared to Unipolar Hemiarthroplasty . 11 out of 16 cases had returned to their premorbid status as community ambulators . Post operative functional outcome in terms of ambulation showed 50 % of patients returning back to their premorbid ambulatory status There was a definite correlation between the incidence of fracture neck of femur and Osteoporosis. In this study, 73.3 % of patients showed evidence of established Osteoporosis. This would support the decision to choose Replacement Arthroplasty rather than Internal fixation in Garden type 3 and 4. The mortality rate in this study was 15.6 % within the first year of operation which is within an acceptable range as compared to other studies which rates was as high as 30 % .